Relative Concerns for Consumption at the Top: An Intertemporal Analysis for the UK - Climent Quintana-Domeque; Johannes Wohlfart (Institute for the Study of Labor (IZA), 2014)
This paper investigates whether the consumption of rich households provides a reference point in the consumption choices of non-rich households from an intertemporal perspective. Using UK household data on food consumption, we estimate the Euler equation implied by a life-cycle model incorporating relative concerns for the consumption of rich households. According to both our OLS and GMM estimates, for the population of non-rich individuals as a whole, there is no evidence of such relative concerns. These results are robust to alternative definitions of the reference group, the presence of exogenous effects and liquidity constraints, and the interval censoring nature of our food consumption data. However, we find some (correlational) evidence of heterogeneous effects across county and household characteristics, which is robust to simultaneous estimation. In particular, there are relative concerns (for consumption at the top) in counties with relatively low income inequality or relatively high population density. Households whose head has relatively low educational attainment are also subject to relative concerns for consumption at the top.
Keywords: D12; D91; 330; keeping up with the Joneses; inequality; trickle-down consumption; UK